Solve the equation 3x^2/3 + x^1/3 − 2 = 0

Let u = x^1/3 

The equation can therefore be written as:

3u^2+u-2=0

This can be factorised to:

(3u-2)(u+1)+0 

Therefore: u = 2/3 or u = -1 OR x^1/3 = 2/3 or x^1/3 = -1

So: x = (2/3)^3 or x = (-1)^3 

x = 8/27 or x = -1

Answered by Namita H. Maths tutor

8751 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate x^(1/2)ln(3x) with respect to x.


Find the intergal of 2x^5 -1/(4x^3) -5 giving each term in its simplest form.


Given y=rootx + 4/rootx = 4, find the value of dy/dx when x=8, writing your answer in the form aroot2, where a is a rational number.


given that y = 1 when x = π, find y in terms of x for the differential equation, dy/dx = xycos(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences